The Role of the Quality of Work-Life to Reinforce the Organizational Commitment - بركات, حيان (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This research aimed to examine the relationship between the quality of work-life and the organizational commitment in Syrian Ministry of Transport (Central Administration (. It deals with the quality of work-life during five dimensions: (Physical Work Environment, work compensation, participation in decision, promotion opportunity, the balance between work-life and personal life). Whereas it deals with the organizational commitment during one dimension. The research relied on a questionnaire as a tool for data collection, the researcher chose accidental sample of workers included 70 individuals, 60 valid questionnaires were retrieved, 57 were able to analyze, and the stability of the scale was confirmed through the Cronbach's Alpha coefficient. Moreover, appropriate statistical methods were used to test the hypotheses where the researcher used descriptive statistics, one sample t test and Pearson correlations test. A number of results were reached through testing the hypotheses, include: The answers of the sample’s individuals tend to agree on the existing of organizational commitment, and the quality of work-life dimensions are available with its studied dimensions in Syrian Ministry of Transport (Central Administration (. There is appositive and significant correlation relationship that is medium strength between organizational commitment and the Physical work environment, while the relationship with the rest of the studied dimensions is an appositive and significant correlation but weak-strength in Syrian Ministry of Transport (Central Administration).